Gestational weight gain and body mass indexes have an impact on the outcomes of diabetic mothers and infants. (November 2015) - Maayan‐Metzger, Ayala; Schushan‐Eisen, Irit; Strauss, Tzipora; Globus, Omer; Leibovitch, Leah
Abstract Aim This study evaluated mothers with diabetes to determine whether prepregnancy body mass index (BMI), BMI on delivery or gestational weight gain (GWG) had the greatest impact on maternal and neonatal outcomes. Methods We retrospectively examined the medical charts of 634 full‐term infants born to mothers with gestational diabetes mellitus not requiring insulin (n = 476), gestational diabetes mellitus requiring insulin (n = 140) and insulin‐dependent diabetes mellitus (n = 18). Data regarding maternal BMI before pregnancy and on delivery were recorded, as well as maternal and neonatal complications. Results Infants born to women who gained more than the recommended weight during pregnancy had higher birthweights, higher rates of meconium‐stained amniotic fluid and neonatal hypoglycaemia. Using logistic regression, Caesarean section delivery was predicted by gestational diabetes requiring insulin, with an odds ratio (OR) of 1.76, maternal hypertension (OR 2.4), infants born large for gestational age (OR 2.78) and maternal BMI ≥30 on delivery (OR 1.06). Neonatal complications were predicted by maternal insulin‐dependent diabetes (OR 5.21), lower gestational age (OR 0.8) and GWG above the recommended amount (OR 1.56). Conclusion Women with diabetes should be made aware that higher GWG can lead to Caesarean section delivery, infant macrosomia and other neonatal complications.